Squamous lesions with glandular involvement: conventional cytology versus liquid-based cytology - Oliveira, Telma; Azevedo, Vera; Dominguez, Rute (Citotech Online - Case Review, 2017)
Portugal is the Western European country with the highest incidence rate of cervical cancer, being the Human Papillomavirus (HPV) infection its main cause. Cervical cytology is the most widely used screening method for the prevention and detection of cervical cancer, either by conventional means or by liquid basis. Conventional cytological preparations have more limitations than liquid-based preparations, however, when dealing with glandular lesions, both conventional and liquid-based cytology have some drawbacks. We report the case of a 31-year-old woman whose results from the screening cytology tests diverge from histological diagnosis. With this study we intend to highlight the limitations of conventional cytology in relation to the liquid-based cytology in the diagnostic of glandular lesions.